Safety of tiotropium/olodaterol in chronic obstructive pulmonary disease: pooled analysis of three large, 52-week, randomized clinical trials. (October 2018) - Ferguson, Gary T.; Buhl, Roland; Bothner, Ulrich; Hoz, Alberto de la; Voß, Florian; Anzueto, Antonio; Calverley, Peter M.A.
Abstract: Background: An extensive clinical trial program supports the efficacy and safety of tiotropium/olodaterol in chronic obstructive pulmonary disease (COPD). We examined the safety of tiotropium/olodaterol compared with tiotropium in a large population of patients, focusing on cardiovascular and respiratory events. Methods: Patients (n = 9942) who received once-daily tiotropium/olodaterol 5/5 μg or tiotropium 5 μg (via Respimat ® ) in TONADO 1 & 2 and DYNAGITO were included. The number of patients and exposure-adjusted rate of events are presented for adverse events (AEs), serious AEs (SAEs), AEs leading to discontinuation, and cardiovascular and respiratory events. Findings: Fewer patients discontinued due to AEs with tiotropium/olodaterol (5.9%) versus tiotropium (7.9%; rate ratio [RR] 0.72; 95% confidence interval [CI] 0.62–0.84). There was no significant difference in the incidence of AEs, SAEs, cardiovascular AEs or central nervous system vascular AEs between treatments. Incidences of major adverse cardiovascular events (MACE) were 2.11 per 100 patient-years with tiotropium/olodaterol and 2.22 with tiotropium (RR 0.95; 95% CI 0.72–1.25), and incidences of fatal MACE (including death with undetermined cause) were 0.91 and 1.00 per 100 patient-years with tiotropium/olodaterol and tiotropium, respectively (RR 0.91; 95% CI 0.60–1.37). Respiratory AEs were generally balanced between treatment groups. Conclusions: These results provide robust evidence that the benefits of tiotropium/olodaterol versus tiotropium are not at the expense of an increased risk of safety events. The combination is a suitable option for patients with COPD, even in the presence of cardiovascular risk factors. Clinical trials registration: clinicaltrials. gov (TONADO 1 and 2: NCT01431274, NCT01431287; DYNAGITO: NCT02296138). Graphical abstract: